NURCHOLISH MADJID: KONSEP MODERNISASI PENDIDIKAN ISLAM - Rikil Rikil Amri; Wasehudin Wasehudin (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
This study aims to examine the concept of modernization of Islamic education in the perspective of Nurcholish Madjid. Because, the basic problem that occurs almost evenly in the world of Indonesian education today is the separation of educational institutions that have different concentrations and orientations. The reality of this educational institution is better known as educational dualism. This type of research is in the form of library research and the type of data used is qualitative. The modernization of education initiated by Nurcholish Madjid can basically be seen through: 1) Historical basis, referring to the growth of philosophical thinking methods and reviving the Islamic scientific ethos which in the classical period of Islam has shown quite brilliant results. 2) The philosophical basis, the responsibility of Islamic education is more emphasized on its manifestation in giving birth to humans who are aware of their existence as God's caliph on earth, such as: leadership of Islamic education and Indonesian human resources.